Reconstructing Ashʿarite Kalam Methodology through Bayani–Burhani–Irfani Integration: An Integrative Review of Contemporary Sunni Theology - Nanang Zamroji; Moh. Asror Yusuf; Zayad Abd. Rahman (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2026)
This article examines methodological renewal in Ashʿarite kalam by developing a more explicit conceptual model of epistemological reconstruction. Using an integrative review, the study analyzes 50 core sources selected from classical theological works, peer-reviewed journal articles, and international academic books published mainly between 2000 and 2026, with classical texts used as foundational references. The review asks how Bayani, Burhani, and irfani epistemologies can be operationalized to transform Ashʿarite kalam from a primarily defensive-dialectical discipline into a reconstructive, dialogical, and ethically responsive theology. In response to the need for clearer library-research reporting, the findings are presented through a coding matrix that maps title/author/year, data source or object, conceptual focus, main findings, and thematic codes. The findings produce a triadic reconstruction model: Bayani functions as textual anchoring, Burhani as rational-coherence testing, and irfani as ethical-spiritual orientation. The novelty of this article lies not in repeating the general integration of Islamic epistemologies, but in translating al-jabiri’s epistemic categories into an operational model for contemporary Ashʿarite theological reasoning. This model clarifies how classical Sunni theology can engage modern issues such as scientific rationality, pluralism, human dignity, and technology ethics without abandoning its doctrinal identity.